2010
DOI: 10.4314/afsci.v4i1.61662
|View full text |Cite
|
Sign up to set email alerts
|

Croissance et capacité reproductive d’<i>Hypnea musciformis</i> (Rhodophyceae, Gigartinale) de la côte atlantique marocaine

Abstract: Growth and reproductuive capacity of Hypnea musciformis (Rhodophyceae, Gigartinale) on the Moroccan Atlantic coast Carrageenan producing seaweeds represent an important biomass along the Atlantic coast of Morocco and are exported as raw material without any local transformation, while agar industry is well developed in the country. The aim of the present work is the valorisation of the more abundant seaweeds and their local transformation. Hypnea musciformis is one of the species studied in the laboratory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…Female and male gametophytes of the "nigrescens" variant were frequently found throughout the sampling period. This observation contradicts those of most previous studies of the "musciformis" variant in Brazil (Schenkman 1989;Wallner et al 1992;Reis & Yoneshigue-Valentin 2000;Caires et al 2013b), and those of other Hypnea species throughout the world (Rao 1977;Rangaiah & Rao 1983;Kong & Ang Jr. 2004;Mouradi et al 2008), in which gametophytes were reported to be rare or absent. Already the vegetative fronds were found only in August 2013, despite representing a considerable proportion (~20 %) of the total biomass collected during this month.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Female and male gametophytes of the "nigrescens" variant were frequently found throughout the sampling period. This observation contradicts those of most previous studies of the "musciformis" variant in Brazil (Schenkman 1989;Wallner et al 1992;Reis & Yoneshigue-Valentin 2000;Caires et al 2013b), and those of other Hypnea species throughout the world (Rao 1977;Rangaiah & Rao 1983;Kong & Ang Jr. 2004;Mouradi et al 2008), in which gametophytes were reported to be rare or absent. Already the vegetative fronds were found only in August 2013, despite representing a considerable proportion (~20 %) of the total biomass collected during this month.…”
Section: Discussioncontrasting
confidence: 93%
“…Regarding the reproductive phenology of the "nigrescens" population studied herein, the highest proportion of the total biomass was observed to be made up by tetrasporophytes, followed by female and male gametophytes, and then by vegetative fronds. According to Cecere et al (2000), the dominance of populations by the tetrasporophyte appears to be very common in red algae, and this was also previously reported in natural populations of Hypnea species (Rangaiah & Rao 1983;Schenkman 1989;Wallner et al 1992;Faccini & Berchez 2000;Reis & Yoneshigue-Valentin 2000;Kong & Ang Jr. 2004;Mouradi et al 2008;Caires et al 2013b). Two main hypotheses can explain the predominant occurrence of the tetrasporophytic phase in Hypnea populations: (1) tetrasporophytes may produce more upright thalli per plant and are thus more robust under stressful conditions (Mathieson 1989); or (2) populations maintain themselves mainly by vegetative reproduction (Schenkman 1989).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, knowledge of the fertility period will allow establishing a management plan to conserve the species. limited to harvesting and raw material (Mouradi et al, 2008).The carrageenan industry has not experienced a development such as that of the agarophyte algae industry, which represents the leading industrial activity placing Morocco among the world's important producers (El Mtili et al, 2013;Hanif et al, 2014).The main commercial species are Chondracanthus acicularis (C. acicularis) (Roth) Fredericq 1993, Chondracanthus teedei (C. teedii) (Mertens ex Roth) Kützing 1843 and Gigartinapis tillata (G. pistillata) (S.G. G melin) Stackhouse1809, due to the highest carrageenan yields (Pereira, 2013). These three species are characterized by different morphological aspects and can live in the same biotope; however, they are harvested or picked up without distinguishing them from one to another (Guiry, 1984a).Chondracanthus species are characterized by having multiaxial erect thalli emerging from a discoid crustose holdfast, and growth by means of apical or marginal meristems (Bulboa Contador et al, 2020).…”
Section: Introductionmentioning
confidence: 99%